The feasibility and safety of a through-and-through wire technique for central venous occlusion in dialysis patients. Issue 1 (December 2016) - Huang, Yonghui; Chen, Bing; Tan, Guosheng; Cheng, Gang; Zhang, Yi; Li, Jiaping; Yang, Jianyong
Abstract Background To retrospectively compare the operation time, success rate and efficacy between unidirectional and bidirectional procedures in the treatment of central venous occlusion diseases (CVOD), assess the advantages of the bidirectional approach, and determine the characteristics of CVOD appropriate for the bidirectional approach treatment. Methods A total of 49 patients who underwent endovascular interventions with all relevant data between January 2011 and December 2015 at the First Affiliated Hospital, Sun Yat-sen University, Guangzhou, China, were included in this retrospective study, and were categorized into two groups: the 19 patients in group 1 had undergone percutaneous transluminal venoplasty (PTV) via a conventional technique (unidirectional procedure from the vein distal or proximal to the obstructive lesion), and the 30 in group 2 had undergone flossing wire technique (bidirectional procedure from femoral vein and the vein distal to obstructive lesion and using a flossing wire technique). The technical success rate, the fluoroscopy time in the procedure, perioperative complications, and patency were evaluated retrospectively. Results Compared with group 1, group 2 had a higher initial technical success rate (83.33% vs. 47.36%, p = 0.012) but a shorter fluoroscopy time (82.6 ± 26.1 vs. 116.1 ± 42.1, p = 0.048). Receiver operating characteristic (ROC) analysis indicated that a lesion with a length of 6.5 cm was the best predictor of technique success (p = 0.02) in group 1, but no cut-off value was identified for group 2. There were no significant differences in perioperative complications between these two groups. The complication rates were 31.58% (6/19) in group 1 and 6.67% (2/30) in group 2, (p = 0.043), respectively. No significant difference was observed between these two groups with respect to the stent patency rate. Conclusion Compared with the conventional technique, the flossing wire technique has a higher success rate, shorter fluoroscopy time, fewer complications and similar patency rate. It is a feasible treatment for CVOD, especially for long obstructive lesions.